Keterbukaan Diri dalam Pengembangan Karir Anggota Paguyuban Mojang Jajaka Kota Cimahi - Nandika, Humaira Putri; El Karimah, Kismiyati; Octavianti, Meria (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the phenomenon of self-disclosure in career development among members of the Paguyuban Mojang Jajaka in Cimahi City. Using a descriptive qualitative method with data collection techniques such as observation interviews and literature review, this research explores the reasons and processes of information exchange among the members of the organization related to career development. The findings indicate that the members share information to enhance skills, strengthen self-image, exchange job opportunities, and understand the challenges and weaknesses they face. The process of information exchange involves interpersonal communication supported by honesty, which ultimately builds trust and strengthens relationships among members. The media used in this information exchange process are WhatsApp and Instagram. This study shows that open communication within the context of social organizations like paguyuban can support the career development of its members.